Effects of citric acid and heterofermentative inoculants on anaerobic co-fermentation of Chinese cabbage waste and wheat bran. (June 2023) - Li, Jiawei; Jia, Shuo; Ma, Dongbo; Deng, Xianglong; Tian, Jiahui; Wang, Ruixue; Li, Jianping; Shan, Anshan
Graphical abstract: Highlights: Obligately heterofermentative Lactobacillus promoted the organic acid production. Citric acid addition into inoculants improved the acetic acid concentration. The combined treatment achieved the highest yield of organic acids. The highest organic acid production was 225.41 g/kg dry matter. The combined treatment stimulated obligately heterofermentative microbes. Abstract: The effects of Lactobacillus buchneri, Lactobacillus hilgardii and citric acid on organic acid production, substrate consumption, protein degradation and microbial community were investigated in this study. The results indicated that combined inoculants induced a significant increase in levels of lactic acid (43 g/kg dry matter), acetic acid (14 g/kg dry matter), butyric acid (5 g/kg dry matter), total organic acid (60 g/kg dry matter) and ammonia nitrogen (20 g/kg total nitrogen). Furthermore, citric acid addition into the combined inoculants caused a significant increase in levels of acetic acid (12 g/kg dry matter), water-soluble carbohydrate (12 g/kg dry matter) and a reduction in ammonia nitrogen formation (22 g/kg total nitrogen). Microbiologically, combining inoculants and citric acid enriched Lactobacillus buchneri and Lactobacillus hilgardii and upregulated the functional pathways related to acid production and resistance. Collectively, combining citric acid and heterofermentative inoculants was beneficial to recycle Chinese cabbage waste in producing organic acids.